The Concept of Dihliz in the Sufi Philosophy of Kiai Achmad Asrori al-Ishaqi: Bridging Traditionality and Modernity in Religious Practices in Indonesia - Wahyudi, Chafid; Zuhri, Achmad Muhibin; Yaqin, Ainul; Ramadhani, Moch. Rafly Try (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2025)
Studies on Nusantara Sufism often treat tarekat communities as socio cultural phenomena and overlook their potential as sources of epistemological innovation. This gap limits understanding of how Sufi traditions generate knowledge that negotiates textual authority and spiritual experience. This article examines the concept of dihliz in KH Achmad Asrori al Ishaqi’s al Muntakhabat to propose a model of liminal Sufi epistemology. The study uses qualitative literature based data drawn from al Muntakhabat as the primary source, supported by secondary works on Sufism and Nusantara intellectual history. The analysis combines hermeneutics to interpret textual meaning and anthropology to situate the text as a cultural artefact, supported by Foucault’s archaeology of knowledge and Bourdieu’s theory of habitus. The findings show three key points. First, dihliz functions as an epistemic threshold that regulates the transition between sharia-based normativity and Sufi experiential knowledge. Second, it produces a hybrid epistemology that integrates rational reflection, textual authority, and intuitive insight. Third, dihliz shapes an epistemic habitus within the tarekat community, enabling the negotiation of tradition and modernity in contemporary religious practice. These findings demonstrate that dihliz offers a conceptual framework for understanding Sufism as a dynamic mode of knowledge production. The study concludes that dihliz provides a useful model for strengthening religious literacy, reconciling doctrinal differences, and supporting peace oriented Islamic education. Future research may apply this framework to other Nusantara Sufi texts to map broader patterns of liminal epistemology.